PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ARITMATIKA SOSIAL DI KELAS VII B SMP NEGERI 20 SIGI: Application of Problem Based Learning (PBL) Model to Improve Students' Learning Outcomes on Social Arithmetics Material in Class VII B of SMP Negeri 20 Sigi - Suprianto Suprianto; Sutji Rochaminah; Muh. Hasbi (Universitas Tadulako, 2025)
This research aim to obtain a description about application of problem based learning (PBL) that can improve students learning outcomes on Social Arithmetic especially on the subject matter of single interest as well as Gross, Tare and Net in class VII B SMP Negeri 20 Sigi. The type of this research is classroom action research. The design of this research referred to Kemmis and Mc. Teggart’s design. This research was conducted in two cycles. The results of this research indicating that through the application of PBL that can improve student learning outcomes, by following the steps, as follow (1) orientation the students at the problem by providing examples related to Social Arithmetic material in everyday life, (2) organize the students to learn, (3) assist in the investigation of individual and group, (4) develop and present work result, (5) analyze and evaluate problem-solving process.